Prediction-Related Frontal-Temporal Network for Omission Mismatch Activity in the Macaque Monkey - Suda, Yuki; Tada, Mariko; Matsuo, Takeshi; Kawasaki, Keisuke; Saigusa, Takeshi; Ishida, Maho; Mitsui, Tetsuo; Kumano, Hironori; Kirihara, Kenji; Suzuki, Takafumi; Matsumoto, Kenji; Hasegawa, Isao; et al. (Frontiers in Psychiatry, 2022)
Sensory prediction is considered an important element of mismatch negativity (MMN) whose reduction is well known in patients with schizophrenia. Omission MMN is a variant of the MMN which is elicited by the absence of a tone previously sequentially presented. Omission MMN can eliminate the effects of sound differences in typical oddball paradigms and affords the opportunity to identify prediction-related signals in the brain. Auditory predictions are thought to reflect bottom-up and top-down processing within hierarchically organized auditory areas. However, the communications between the various subregions of the auditory cortex and the prefrontal cortex that generate and communicate sensory prediction-related signals remain poorly understood. To explore how the frontal and temporal cortices communicate for the generation and propagation of such signals, we investigated the response in the omission paradigm using electrocorticogram (ECoG) electrodes implanted in the temporal, lateral prefrontal, and orbitofrontal cortices of macaque monkeys. We recorded ECoG data from three monkeys during the omission paradigm, and examined the functional connectivity between the temporal and frontal cortices by calculating phase-locking values (PLVs). This revealed that theta- (4–8 Hz), alpha- (8-12 Hz) and low beta- (12-25 Hz) band synchronization increased at tone onset between the higher auditory cortex and the frontal pole where an early omission response was observed in the event-related potential (ERP). These synchronizations were absent when the tone was omitted. Conversely, low beta-band (12-25 Hz) oscillation then became stronger for tone omission than for tone presentation approximately 200ms after tone onset. The results suggest that auditory input is propagated to the frontal pole via the higher auditory cortex and that a reciprocal network may be involved in generation of auditory prediction and prediction error. As impairments of prediction may underlie MMN reduction in patients with schizophrenia, an aberrant hierarchical temporal-frontal network might be related to this pathological condition.